Negotiating existential concerns through the grotesque in Yukio Mihsima’s forbidden colours - Jin, Beng Seach; Ali Termizi, Arbaayah (UPM Press, 2021)
The grotesque and existential concerns are rarely studied alongside each other in the field of literature. History has it that the grotesque is always associated with aspects which denote negative connotations such as deformity, death, violence or monstrosity. Additionally, the grotesque is also popularly employed as an approach to challenge traditions and deviate from what is accepted as the norm. Meanwhile, the origins of existentialism can be traced back to as early as the 19th century. Existentialists’ main concerns have always been seeking the meaning of life and they are constantly looking for ways to justify one’s existence in a world where pessimism rules. Thus, this paper aims to establish a connection between existentialism and the grotesque by primarily focusing on how the two male protagonists Yuichi and Shunsuke in Yukio Mishima’s Forbidden Colours employ the grotesque as a way to deal with existential concerns as pointed out by Irvin Yalom namely death, meaninglessness, freedom and existential isolation with an emphasis on the first two concerns. Grotesque elements such as misogyny, pederasty and carnivalesque will be studied alongside two existential concerns which are death and meaninglessness to show how the male protagonists are able to rely on the grotesque to subdue their anxieties brought upon by their existential concerns in order to justify their sense of existence.